ENTERIC FEVER IN SULAIMANI PEDIATRIC TEACHING HOSPITAL: RISK FACTORS, PRESENTATION, AND DRUG SUSCEPTIBILITY - Mohammed, Mohammed S; Omer, Sherko A; Rashid, Bakir R; Hamawandi, Adnan M (Journal of Sulaimani Medical College, 2014)
Background Enteric fever is a severe systemic illness characterized by fever and abdominal pain that is caused by dissemination of typhoid Salmonella serovar, Typhi and Paratyphi. These organisms have no known hosts other than humans. Most commonly, foodborne or waterborne transmission occurs as a result of faecal contamination by ill or asymptomatic chronic carriers. Objectives The aim of this study was to determine the risk factors, clinical features in paediatric enteric fever infections along with the antimicrobial susceptibility pattern of the causative agents. Patients and methods This is a prospective-hospital based study, done in Sulaimani Paediatric Teaching Hospital. During the study period 250 cases suspected to have typhoid fever were admitted over a period of 3 month from 1st May-1st Augusts 2008; 95 cases with positive blood culture for typhoid were studied for clinical presentation, risk factors and drug susceptibility of isolates in comparison with a control group. Salmonella strains were identified based on their biochemical properties and antimicrobial susceptibility was determined with Kirby- Bauer disk diffusion method. Results Out of 250 clinically suspected cases of enteric fever, only 95 (38%) were culture positive for Salmonella. The antimicrobial susceptibility of isolate showed that more than 97% of the isolates were resistant to chloramphenicol, ampicillin and co-trimoxazole. Significant risk factors were eating food outside home (P=0.001, OR, 10.788; 95%, CI: 4.292 -27.112), low socioeconomic status (P=0.017, OR 0.437, 95%, CI: 0.229 -0.832), and household contact (P=0.001, OR=15.864, 95% CI: 6.648 -37.854). Conclusion Enteric fever remains one of the endemic febrile illnesses among paediatric age in our community and mainly caused by multi drug resistant Salmonella sereovar Typhi. The most common symptoms indicating infection were fever, headache, vomiting and abdominal pain. Risk factors were eating food outside home, low socioeconomic status and household contact with index cases.
Keywords: Enteric Fever; Salmonella; Risk factor; paediatric infection; Sulaimani